Radical retropubic prostatectomy a review of the current Literature and a study of 250 cases at Marmara University - (:unkn) unknown (My University, 2011)
Amaç: Açık radikal retropubik prostatektomi hakkındaki güncel literatürün derlenmesi ve üniversite kliniğimizde yapılan son 250 açık radikal retropubik prostatektomi vakalarının sonuçlarının bildirilmesi. Materyal ve Metot: Radikal prostatektomi, açık retropubik, prostat kanseri, komplikasyonlar ve komorbidite anahtar kelimeleri seçildi ve Pubmed veritabanı kullanılarak literatür taraması yapıldı. Marmara Üniversitesi Tıp Fakültesi Üroloji Anabilim Dalında yapılan son 250 açık radikal retropubik prostatektomi vakasının dosyaları tarandı. Bulgular: Hastaların % 69, 2sinde tümör prostat bezi ile sınırlı kalırken, % 30.8inde pozitif cerrahi sınır, kapsül invazyonu, seminal vezikül invazyonu ya da bunların kombinasyonu saptandı. Sinir koruyucu radikal retropubik prostatektomi hastalarının ameliyat sonrası dönemde idrar kontinansını ve erektil işlevi geri kazanmalarının daha başarılı olduğu saptandı. Radikal retropubik prostatektomi sonrası vakaların % 12, 4ünde ortalama 53,8 aylık takip ve ortalama 20,7 ay progresyon süresi ile kanser progresyonu saptandı. Sonuç: Radikal prostatektominin üç hedefi olan; kanser kontrolü, idrar kontrolünün korunması ve cinsel işlevin korunması hedeflerine, açık radikal retropubik prostatektominin uzun dönem tecrübesi ile ulaşılmıştır.

Objective: To review the current literature of open radical retropubic prostatectomy and report the results of the last 250 open radical retropubic prostatectomies performed in our University clinic. Patients and Methods: A literature review was performed using the PubMed database with combinations of the following keywords radical prostatectomy, open retropubic, prostate cancer, complications and comorbidity. Charts of the most recent 250 consecutive patients who had undergone radical retropubic prostatectomy at the Urology Department of Marmara University School of Medicine were reviewed. Results: In 69.2% of the cases the tumor was confined within the prostate gland, whereas 30.8% of the cases had tumors with either positive surgical margins, capsular penetration, invasion of seminal vesicles or a combination of these features. Nerve-sparing radical retropubic prostatectomy patients were found to be more successful in achieving continence and erectile function in the post operative period. Cancer progressions were experienced in 12.4% of the cases following radical retropubic prostatectomy at a mean follow-up of 53.8 months with a mean time to progression of 20.7 months. Conclusion: The three goals of radical prostatectomy; cancer control, preservation of urinary control and preservation of sexual function were achieved with the long-time experience of open radical prostatectomy.
Radikal retropubik prostatektomi güncel literatür derlemesi ve son 250 vaka ile Marmara tecrübesi
Keywords: Genel ve Dahili Tıp